HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP STATUS ANEMIA PADA REMAJA PEREMPUAN DI MAN 1 PADANG TAHUN 2024 - Anggraini, Debie; Madina Munawaroh; Roland Helmizar (Yayasan Nusantara Hasana Berdikari, 2025)
Anemia is a condition in which hemoglobin (Hb) or red blood cell levels are lower than normal, generally due to iron deficiency. Hb plays an important role in delivering oxygen and nutrients to the body. The prevalence of anaemia in women aged ≥15 years is high globally, with Southeast Asia as the most common region. In Indonesia, anemia in adolescent girls is increasing, impacting growth, development, learning, and achievement. This study examines the relationship between knowledge and attitudes with anemia in MAN 1 Padang. The selection of MAN 1 Kuranji Padang was based on the high prevalence of anemia in the area, although there had been no similar research before. This study seeks the relationship between knowledge and attitudes towards anemia status in adolescent girls in MAN 1 Padang in 2024. The study used a cross-sectional design with primary and secondary data through purposive sampling techniques. The results showed that out of 87 respondents, 51 people (58.6%) had anemia, with the majority aged 16 years (79 people, 90.8%). The level of knowledge and attitude towards anemia was mostly in the poor category, as many as 54 people (62.1%) and 52 people (59.8%), respectively. Data analysis showed that there was a significant relationship between knowledge and attitude and anemia status (P-value 0.00 < 0.05). Most adolescent girls in MAN 1 Padang have a low level of knowledge and attitude towards anemia, which is related to the high prevalence of anemia in this group.